Novel strategy for the facile enrichment of isopentenyl pyrophosphate in rat plasma via Ti4+‐immobilized polydopamine@Fe3O4 core–shell microspheres. Issue 10 (20th April 2017) - Xu, Chen; Yu, Yingjia; Ling, Li; Sun, Xueni; Li, Yan; Duan, Gengli
Abstract : In this paper, a facile extraction strategy is reported for the analysis of isopentenyl pyrophosphate, a key isoprenoid, based on magnetic core–shell microspheres with Ti 4+ ion exterior walls coupled with liquid chromatography and tandem mass spectrometry. Because of their excellent hydrophilicity and biological compatibility, the polydopamine@Fe3 O4 ‐Ti 4+ microspheres display ideal isopentenyl pyrophosphate extraction efficiency. The technique includes three steps: sample loading, nonphosphate washing, and phosphate elution. Moreover, the microspheres can be regenerated by thorough washing with a specific solvent and can be reused multiple times. The liquid chromatography with tandem mass spectrometry separation was performed on a Welch Ultimate® XB‐C18 column with a total chromatographic analysis time of 5 min; the analytical recovery was 98.52%. The proposed method was used to determine the isopentenyl pyrophosphate concentration in rat plasma samples collected from the Shanghai Chest Hospital. The results indicate the prospective value of the as‐made microspheres for the sensitive and selective enrichment of phosphate compounds in complicated matrices.